Fiscal Policies for a Sustainable Recovery and a Green Transformation - Catalano, Michele (World Bank, Washington, DC, 2021)
This paper compares the effectiveness of different fiscal policy instruments—carbon pricing, fiscal incentives for private green investments, and public green investment—in supporting a green recovery that is also fiscally sustainable. It argues that relying on carbon pricing or green investments is not sufficient to achieve the transition to a low-carbon economy in a timely and sustainable way. Carbon pricing alone would result in rapid and significant energy price increases that would be recessionary. Similarly, the level of public green investment needed to reach the Paris goals without recourse to carbon pricing would be so great that it would endanger debt sustainability. The conclusion from the simulations supports the view that a mix of supply-side policies (carbon pricing) and demand-side interventions (deficit financed green public investment) is necessary to achieve the Paris goals within the specified period and with a fiscally sustainable outcome. The paper also assesses the costs associated with transitioning to a low-carbon economy by geographic area. It finds that deficit financed public green investment by high-emitting countries only (typically advanced and emerging economies), would have positive growth impacts for those countries and enhance their fiscal sustainability, while also providing large positive spillovers to other countries, particularly to highly climate sensitive nations. In turn, the simulations show that wherever fiscally feasible it is in the best interest of all countries to increase public investment in the green economy.